Kedudukan Hukum Surat Keterangan Penguasaan Tanah Sebagai Bukti Kepemilikan Di Kabupaten Karo - May Linda Sari (Jurnal Hukum Kaidah: Media Komunikasi dan Informasi Hukum dan Masyarakat, 2022)
One of the obstacles often faced by the people of Karo Regency in terms of land registration for the first time is the absence of authentic proof of legal land ownership, in the form of a Land Tenure Certificate (SKPT). In general, they get land management from the customary leader without written evidence. Land management in Tanah Karo is basically communal or shared use regulated by the Customary Stakeholders. As long as the payment goes well, land tenure will continue, because this is evidence of land tenure given to the community. This phenomenon underlies the research problem regarding how the legal position of the SKPT is as proof of ownership in Karo Regency.This study uses field research with a descriptive qualitative analysis approach and was conducted in Karo Regency, North Sumatra.The type of this research is qualitative. Primary data was collected through observation and interviews, while secondary data was collected through library research and documentation.The results showed that there are 2 (two) types of SKPT as regulated in Government Regulation no. 24 year 1997 concerning Land Registration, namely Proof of Old Rights (Article 24 PP 24/1997) and Proof of New Rights (Article 23 PP 24/1997). However, for the conversion of Ownership Rights, SKPT requires strengthening of witnesses and land tenure is not intended for things that are prohibited by law and are not in dispute. Suggestions in this study are the need for education to the public about the importance of proof of land tenure as evidence in landregistration for the first time. People who control the SKPT but have not registered it must manage their land properly, not to be controlled by a third party. The Karo Regency Land Office needs to socialize about legal remedies that can be taken by the community when the rights they get are weak.